The X‐ray structure of l‐threonine dehydrogenase from the common hospital pathogen Clostridium difficile. Issue 8 (28th July 2021) - Adjogatse, Eyram; Bennett, Josh; Guo, Jingxu; Erskine, Peter T.; Wood, Steve P.; Wren, Brendan W.; Cooper, Jonathan B.
Abstract : The l ‐threonine dehydrogenase from Clostridium difficile has been cloned, expressed and crystallized, allowing the X‐ray structure to be determined at 2.6 Å resolution with an R factor of 20.0% and an R free of 23.9%. Abstract : In many prokaryotes, the first step of threonine metabolism is catalysed by the enzyme threonine dehydrogenase (TDH), which uses NAD + to oxidize its substrate to 2‐amino‐3‐ketobutyrate. The absence of a functional TDH gene in humans suggests that inhibitors of this enzyme may have therapeutic potential against pathogens which are reliant on this enzyme. Here, TDH from Clostridium difficile has been cloned and overexpressed, and the X‐ray structure of the apoenzyme form has been determined at 2.6 Å resolution.